Association between weekend catch-up sleep and depression in US adults - Lingying Le; Ziwei Lan; Chenxi Chen (BMC Public Health)
Abstract Background Depression is one of the most prevalent mental disorders and causes a serious economic and medical burden on society. This research assessed the correlation between weekend catch-up sleep (WCS) and depression in US adults aged ≥ 20 years. Methods Cross-sectional data were obtained from individuals with complete WCS and Patient Health Questionnaire (PHQ-9) data who participated in the 2017–2020 National Health and Nutrition Examination Survey (NHANES). A logistic regression analysis was conducted to evaluate the possible independent conjunction between depression and WCS. Subgroup analysis and interaction tests have been carried out. Results A total of 7,795 individuals with an average PHQ-9 level of 3.27 ± 4.25 were analyzed. The prevalence of depression was 9.11% overall, and participants in the quartile 3 (WCS 1–2 h) tended to have lowest rates of depression (Quartile 1: 9.49%; Quartile 2: 9.95%; Quartile 3: 7.03%; Quartile 4: 8.75%; p = 0.014). The incidence of depression was found to be less correlated with 1–2 h of WCS (OR = 0.74, 95% CI: 0.55, 0.99). Individuals with less than one hour or more than two hours of WCS did not have a significantly different risk of depression than individuals without WCS. Conclusions Moderate catch-up sleep on weekends was linked to a decreased likelihood of depression.